Analysis of the Technology Acceptance Model for Paid E-Learning Applications during the Covid-19 Pandemic - Muhammad Ardiansyah; Sanusi; Ilham Juliwardi; Mirna Ria Andini; Fachruddin; Muhammad Usman (LPPM Politeknik Aceh Selatan, 2023)
The aim of this research is to analyze student perceptions of the use of e-learning platforms in learning. The type of research used is descriptive quantitative. The sample in this research was 57 students from the information technology study program in 2020. The data collection technique in this research uses a questionnaire. The data analysis technique uses simple and multiple regression analysis with the help of the Statistical Product for Servicer Solution (SPSS) 21 program. Based on research results from the questionnaire on convenience variables and usefulness variables, then it can be seen that the research results show that the t count is greater than the t table value, the t table value is 2.060 and the t count value is 10.663 for the convenience variable and 7.478 for the usefulness variable. So t count > t table and each independent variable has a significant value < 0.05. As for the results of multiple linear regression analysis, it was also found that the independent variables simultaneously had a positive effect on the dependent variable and were assessed as significant <0.05. This indicates that there is a positive influence of the convenience factor and the usefulness of using e-learning by students in participating in learning during the Covid-19 pandemic.